Focally perfused succinate potentiates brain metabolism in head injury patients. Issue 7 (July 2017) - Jalloh, Ibrahim; Helmy, Adel; Howe, Duncan J; Shannon, Richard J; Grice, Peter; Mason, Andrew; Gallagher, Clare N; Stovell, Matthew G; van der Heide, Susan; Murphy, Michael P; Pickard, John D; Menon, David K; et al.
Following traumatic brain injury, complex cerebral energy perturbations occur. Correlating with unfavourable outcome, high brain extracellular lactate/pyruvate ratio suggests hypoxic metabolism and/or mitochondrial dysfunction. We investigated whether focal administration of succinate, a tricarboxylic acid cycle intermediate interacting directly with the mitochondrial electron transport chain, could improve cerebral metabolism. Microdialysis perfused disodium 2, 3- 13 C2 succinate (12 mmol/L) for 24 h into nine sedated traumatic brain injury patients' brains, with simultaneous microdialysate collection for ISCUS analysis of energy metabolism biomarkers (nine patients) and nuclear magnetic resonance of 13 C-labelled metabolites (six patients). Metabolites 2, 3- 13 C2 malate and 2, 3- 13 C2 glutamine indicated tricarboxylic acid cycle metabolism, and 2, 3- 13 C2 lactate suggested tricarboxylic acid cycle spinout of pyruvate (by malic enzyme or phosphoenolpyruvate carboxykinase and pyruvate kinase), then lactate dehydrogenase-mediated conversion to lactate. Versus baseline, succinate perfusion significantly decreased lactate/pyruvate ratio (p = 0.015), mean difference −12%, due to increased pyruvate concentration (+17%); lactate changed little (−3%); concentrations decreased for glutamate (−43%) (p = 0.018) and glucose (−15%) (p = 0.038). Lower lactate/pyruvate ratio suggests better redox status: cytosolic NADH recycled to NAD + by mitochondrial shuttles (malate-aspartate and/or glycerol 3-phosphate), diminishing lactate dehydrogenase-mediated pyruvate-to-lactate conversion, and lowering glutamate. Glucose decrease suggests improved utilisation. Direct tricarboxylic acid cycle supplementation with 2, 3- 13 C2 succinate improved human traumatic brain injury brain chemistry, indicated by biomarkers and 13 C-labelling patterns in metabolites.